"Why I Chose Hemodialysis over Peritoneal Dialysis": An Opinion Survey among In-Center Hemodialysis Patients. Issue 4 (July 2018) - Valson, Anna T.; Asad, Riyaz A.; Radhakrishnan, Radhika C.; Sinha, Shampa; Jacob, Shibu; Varughese, Santosh; Tamilarasi, Veerasamy
Peritoneal dialysis (PD) penetration in India remains low despite the huge chronic kidney disease burden and unmet need for renal replacement therapy (RRT). In order to understand the socioeconomic reasons that govern patients' preference for hemodialysis (HD), we carried out an opinion survey among prevalent in-center HD patients at our institution using a multiple response questionnaire that was verbally administered to them at the dialysis facility by the investigators. Close to 80% were self-financed and 49.5% were on twice weekly HD. Despite the majority (95%) receiving RRT education from a nephrologist, 43.4% were not aware of PD as an RRT modality. The treating nephrologist's recommendation was the most important reason given for choosing HD (77.8%) and not choosing PD (69.7%). Other reasons for not choosing PD included lack of a dedicated caregiver or "clean area" at home (15.1%), fear of infection (15.1%), disruption of work (14.1%), and the high cost of PD (7%). The perceived advantages of HD over PD were greater convenience because of need for only twice or thrice weekly sessions (61%), supervised care received in a hospital setting (28.8%), and less disruption of the patient's and family's routine (22%). We discuss the implications of these findings and what policy makers and nephrologists in India and other developing countries can do to improve PD penetration and utilization.